PENGARUH DOSIS KOMPOS UNTUK MENINGKATKAN PERTUMBUHAN RUMPUT GAJAH (Penissetum puperium) PADA TANAH TERCEMAR LIMBAH OLI BEKAS - Aisah, Rohmi Aisah; Asmarahman, Ceng; Indriyanto, Indriyanto (MAKILA, 2023)
Used oil is B3 waste (hazardous and toxic material) which can cause soil pollution and reduce soil productivity. The accumulation of metals in the soil caused by waste oil pollution causes a decrease in soil quality and can become a pollutant that affects life around it. There needs to be a way to improve the quality of polluted soil, with phytoremediation techniques and the addition of organic matter to polluted soil. This research aims to analyze the effect of the dose of liquid compost on the growth of elephant grass in soil contaminated with used oil waste. This research used a Completely Randomized Design (CRD) with compost fertilizer factors consisting of 4 dose levels and a total of 60 sample observation units. The research results showed that a 50 ml dose of compost had the best effect on the growth of elephant grass planted on soil contaminated with used oil waste. A dose of 50 ml was proven to increase the growth of elephant grass in the parameters of plant height, number of tillers and fresh shoot weight.